Structure and Constituents of Digital Marketing Systems - Robul, Yuriy (Olsztyn Economic Journal, 2020)
The article addresses the study of digital marketing as a marketing system, the definition of its key elements, feeds and outputs, as well as levels of structure. At the moment, digital marketing is mostly considered at the micro level, while it is functioning at the level of the entire economy, and the systemic interaction between digital marketing and other social subsystems are not well understood. The result of the study is the conceptualization of the digital marketing model as a marketing system and the allocation of three levels of digital marketing. This opens up prospects for a better understanding of the processes of economic development, factors of influence and means to manage.